Morphological Characteristics and Sustainable Adaptive Reuse Strategies of Regional Cultural Architecture: A Case Study of Fenghuang Ancient Town, Xiangxi, China - Jingyi Wang; Safial Aqbar Zakaria (Buildings)
This study explores the application of sustainable adaptive reuse strategies in preserving historical and cultural buildings, with the goal of establishing a scientifically robust framework of indicators for systematic evaluation and practical application. Focusing on the diaojiaolou (stilted buildings) along the Tuojiang River in the ancient town of Fenghuang, the research integrates findings from an extensive literature review with a theoretical framework to propose a multidimensional indicator system encompassing preservation, rehabilitation, urban renewal, adaptive reuse, urban revitalization, and restoration. Through detailed field investigations and comprehensive case studies, the study examines the cultural significance of the stilted buildings, including their spatial organization, structural design, material composition, and decorative features. It also critically assesses the effectiveness of sustainable adaptive reuse strategies in promoting regional development. The findings reveal that these strategies not only preserve the cultural and historical integrity of the stilted buildings but also enhance their functionality to meet modern needs, achieving a balance among heritage conservation, environmental sustainability, and socio-economic progress. This research validates the scientific rigor and practical utility of the proposed six-dimensional indicator framework as an evaluative tool, offering a model for the sustainable development and cultural preservation of similar regional heritage assets.